2008
DOI: 10.1111/j.1752-1688.2007.00150.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship Between Mean and Variance of Soil Moisture Fields1

Abstract: The objective of this work was to explain an apparent contradiction in the literature related to the relationship between mean and variance (or standard deviation) of soil moisture fields. Some studies found an increase in soil moisture variance with decreasing mean soil moisture, while others showed a decrease. The evidence of maximum variance in the mid‐range of mean soil moisture was also reported in the literature. In this paper, we focus on the effects of spatial variability of soil texture on the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 25 publications
3
59
2
Order By: Relevance
“…Furthermore, there was a threshold in the shelterbelt with the value of approximately 22.0%. Pan and Peters-Lidard (2008) indicated that the variance decreased with SWC when it exceeded the threshold, and the variance increased with SWC if it was less than the threshold. In contrast, no evidence of a threshold effect was found in the cropland, desert or cropland-shelterbelt-desert land use pattern.…”
Section: Spatial Variability Of Soil Water Contentmentioning
confidence: 99%
“…Furthermore, there was a threshold in the shelterbelt with the value of approximately 22.0%. Pan and Peters-Lidard (2008) indicated that the variance decreased with SWC when it exceeded the threshold, and the variance increased with SWC if it was less than the threshold. In contrast, no evidence of a threshold effect was found in the cropland, desert or cropland-shelterbelt-desert land use pattern.…”
Section: Spatial Variability Of Soil Water Contentmentioning
confidence: 99%
“…The values of the first two statistical moments of absolute soil moisture data (in volumetric units, m 3 /m 3 ), i.e., mean and variance, as well as their mutual relationship, were largely investigated (e.g., [79]). In most cases, a convex upward relationship is obtained between mean and variance thus concluding that soil moisture variability peaks for intermediates wetness conditions (e.g., [2,75,80,81]).…”
Section: How Does the Soil Moisture Vary In Space And Time?mentioning
confidence: 99%
“…When the mean VSM decreases to a threshold, the dominant process controlling soil drying is switched from drainage to evapotranspiration. With further reduction of mean VSM, CVs are decreased by the effect of evapotranspiration, showing a positive correlation with mean VSM in dry soils [48]. The VSM threshold depends on soil, topography, climate, and vegetation, and is typically between 15% and 25% [48,49].…”
Section: Spatial and Temporal Variability Of Vsmmentioning
confidence: 99%
“…The CVs are mainly controlled by soil hydraulic conductivity and porosity under (extreme) wet conditions. When the mean VSM starts to decrease due to the drainage and evapotranspiration, the variability of saturated hydraulic conductivity, particle size distribution, and air entry pressure will result in an increase in CVs, thus CVs are negatively correlated with the mean VSM in relatively wet conditions [47,48]. When the mean VSM decreases to a threshold, the dominant process controlling soil drying is switched from drainage to evapotranspiration.…”
Section: Spatial and Temporal Variability Of Vsmmentioning
confidence: 99%